1986
DOI: 10.1002/ijc.2910380604
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic composition, age and sex, together with location and standard of housing as determinants of HLTV‐I infection in an urban trinidadian community

Abstract: The presence of antibody to human T-cell leukaemia virus (HLTV-I) has been assessed in 2,143 men and women who represent 83% of all adults aged 35 to 69 years resident in a defined urban community in Trinidad. Individuals of African descent had a higher sero-positivity rate (7.0%) than those originating from India (1.4%), Europe (0%) or of mixed descent (2.7%). Women were infected more frequently than men, and the prevalence of infection increased with age in both sexes. Sero-positivity rates were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 26 publications
2
16
0
2
Order By: Relevance
“…These data suggest that social and environmental factors associated with poverty may influence HTLV-I transmission both within endemic countries and across the world (Miller et al, 1986;Maloney et al, 1991). Similarly, HTLV-I endemic countries (excluding Japan) have low per capita income and have to deal with a higher burden of HTLV-I/II infection and associated diseases with fewer resources than high-income countries.…”
Section: Risk Factors and Routes Of Transmission -Individual And Socimentioning
confidence: 93%
“…These data suggest that social and environmental factors associated with poverty may influence HTLV-I transmission both within endemic countries and across the world (Miller et al, 1986;Maloney et al, 1991). Similarly, HTLV-I endemic countries (excluding Japan) have low per capita income and have to deal with a higher burden of HTLV-I/II infection and associated diseases with fewer resources than high-income countries.…”
Section: Risk Factors and Routes Of Transmission -Individual And Socimentioning
confidence: 93%
“…Studies from Japan (Stuver et al, 1992) have previously documented a strong geographic clustering of HTLV-I, particularly on the island of Kyushu, with rates varying over relatively short distances attributed to migrations from southern Japan to the cities of the north. Similar clusterings have also been described in the Caribbean basin, raising questions about the role of environmental factors, such as river proximity in Trinidad (Miller et al, 1986) or altitude in Jamaica (Maloney et al, 1991).…”
Section: Discussionmentioning
confidence: 81%
“…Recently, however, it was revealed that ATL patients are widely distributed throughout the world (Fig. 3); that is, ATL occurs among blacks in the Caribbean Basin [8][9][10][11], central Africa [12][13][14], and the southeastern part of the United States [15], Melanesian in Papua New Guinea and Vanuatu [16], and whites in southern Italy [17]. In the present paper, epidemiological studies focusing mainly on ATL in Japan are reviewed and compared to other countries.…”
Section: Introductionmentioning
confidence: 99%